2001
DOI: 10.1080/00224540109600586
|View full text |Cite
|
Sign up to set email alerts
|

Personality Attributes of Volunteers and Paid Workers Engaged in Similar Occupational Tasks

Abstract: The authors' primary aim was to determine whether Australian volunteers and paid workers who were engaged in similar activities differed on aspects of a 5-factor model of personality. Their secondary aim was to determine whether personality attributes were similar between volunteers involved in different activities. The participants were 36 volunteer food preparers, 38 paid food preparers, and 31 volunteer firefighters. Each participant completed a personality inventory (P. T. Costa & R. R. McCrae, 1992) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
51
0
11

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 20 publications
5
51
0
11
Order By: Relevance
“…This result is surprising, because agreeableness is positively related to empathic concern, and empathic concern is positively related to civic engagement. Previous research (Elshaug & Metzer, 2001) found that agreeableness was typical of specific groups of volunteers. The results above indicate that agreeableness is not typical of all volunteers and that political idealists are not nice people in daily life.…”
Section: Resources Political Values and Personality Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is surprising, because agreeableness is positively related to empathic concern, and empathic concern is positively related to civic engagement. Previous research (Elshaug & Metzer, 2001) found that agreeableness was typical of specific groups of volunteers. The results above indicate that agreeableness is not typical of all volunteers and that political idealists are not nice people in daily life.…”
Section: Resources Political Values and Personality Characteristicsmentioning
confidence: 99%
“…Verba, Schlozman, and Brady (1995) and Inglehart (1977Inglehart ( , 1996 have shown that interest in politics and postmaterialism increase civic engagement. Personality and social psychologists, on the other hand, are interested in civic engagement, and especially in volunteering behaviors, as an expression of prosocial dispositions such as extraversion, agreeableness, and empathy (Carlo, Allen, & Buhman, 1999;Elshaug & Metzer, 2001;Penner & Finkelstein, 1998;Smith, 1966). Others have investigated the relationship of civic engagement to moral reasoning (Muhlberger, 2000), self-esteem, and locus of control (Cohen, Vigoda, & Samorly, 2001).…”
mentioning
confidence: 99%
“…Adopting a more distal approach, scholars have also applied the five-factor model of personality to the study of volunteering. Agreeableness and extraversion, in particular, have been linked to volunteering direction (Carlo, Okun, Knight, & de Guzman, 2005;Elshaug & Metzer, 2001), indicating that volunteers are likely to be more extraverted and agreeable than nonvolunteers. Yet when examined alongside other individual differences, the Big Five traits showed no effect on volunteering intensity (Erez, Mikulineer, van Ijzendoorn, & Kroonenberg, 2008).…”
Section: Table 1 (Continued)mentioning
confidence: 99%
“…Ово је случај и када су у питању истраживања корелације између особина личности и волонтерског понашања (Elshaug & Metzer, 2001;Spangler & Reynolds, 1991;Bekkers, 2005;Jabari, Boroujerdi, Ghaeini, Abdollahi & Karimi, 2012). Једно могуће објашњење за такве налазе јесте да особине у узајам-ној интеракцији удружено утичу на мотиве, који су, у каузалном смислу, бли-скији исходима у социјалном понашању (Carlo et al, 2005).…”
unclassified